Whatsapp as Da’wah Sipakainge’ Media: Study on Students of UIN Alaudddin Makassar, Indonesia - Mahmuddin (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
This study aims to determine the use of WhatsApp as a media of da'wah sipakainge' for UIN Alauddin Makassar students, by raising the problem, namely how to use WhatsApp for UIN Alauddin students and why WhatsApp is used as a media for da'wah sipakainge' by UIN Alauddin Makassar students. This study examines the problem of using WhatsApp as a medium for preaching sipakainge' for UIN Alauddin Makassar students. This type of research is qualitative research using media, da'wah and sociological approaches as well as communication approaches. The data source of this research is the students of UIN Alauddin Makassar using data collection methods through observation, questionnaires, interviews, and documentation. Data processing and analysis techniques are qualitative descriptive techniques. Based on the results of the research, it shows that students of UIN Alauddin Makassar have used WhatsApp as a media of da'wah for social media ', this was found in a number of questionnaire results and interviews with UIN Alauddin Makasar students, which stated that WhatsApp was a means of communication for students, WhatsApp was a media of da'wah, the use of WA in spreading sipakainge' da'wah, many students use WA in spreading sipakainge' da'wah to individuals or groups. Meanwhile, the reason WhatsApp is used as a medium for preaching sipakainge' by UIN Alauddin students is because of the low cost, because many students access it because it is easy to communicate in groups because it is very easy to find invitations of kindness as material for sipakainge’ da'wah because it is easy to send da'wah material to groups. The implication of this research is the need to utilize and direct students in using WhatsApp in the learning process and use it according to the actual function of creating WhatsApp media as well as possible.